2017
DOI: 10.1016/j.survophthal.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced corneal epithelial changes

Abstract: Drugs across many pharmacologic classes induce corneal epithelial changes. Many of these drugs have cationic amphiphilic structures, with a hydrophobic ring and hydrophilic cationic amine side chain that allow them to cross cell membranes. These drugs lead to intracellular phospholipid accumulation, often manifested in the cornea by vortex keratopathy, with no effect on visual acuity and few ocular symptoms. Other drugs, notably antineoplastic agents, produce a fine diffuse corneal haze, sometimes accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 78 publications
1
79
0
12
Order By: Relevance
“…Cornea verticillata are a common occurrence with amiodarone 30 and other treatments that have been approved by the United States Food and Drug Administration. 29 Cornea verticillata were reported as mild or moderate in all affected ROCKET-4 study participants and were not associated with decreases in visual function; they were only observed at the biomicroscope (ie, patients were asymptomatic and unaware of the presence of cornea verticillata) and resolved following treatment cessation in most (60.5%) affected patients by study end. Conjunctival hemorrhage, which was typically described by investigators as small petechial hemorrhages, was reported as mild or moderate in all cases and generally resolved with continued use of netarsudil.…”
Section: Vol 204mentioning
confidence: 87%
See 1 more Smart Citation
“…Cornea verticillata are a common occurrence with amiodarone 30 and other treatments that have been approved by the United States Food and Drug Administration. 29 Cornea verticillata were reported as mild or moderate in all affected ROCKET-4 study participants and were not associated with decreases in visual function; they were only observed at the biomicroscope (ie, patients were asymptomatic and unaware of the presence of cornea verticillata) and resolved following treatment cessation in most (60.5%) affected patients by study end. Conjunctival hemorrhage, which was typically described by investigators as small petechial hemorrhages, was reported as mild or moderate in all cases and generally resolved with continued use of netarsudil.…”
Section: Vol 204mentioning
confidence: 87%
“…They form through a process known as phospholipidosis, which occurs when cationic amphiphilic drugs such as netarsudil complex with lysosomal phospholipids. [27][28][29] They are a result of the chemical properties of the drug and are not metabolic in nature. Cornea verticillata are a common occurrence with amiodarone 30 and other treatments that have been approved by the United States Food and Drug Administration.…”
Section: Vol 204mentioning
confidence: 99%
“…Cornea verticillata forms through a process known as phospholipidosis, which occurs when cationic amphiphilic drugs like netarsudil bind to lysosomal phospholipids. [32][33][34] The development of cornea verticillata is associated with systemic amiodarone and other U.S. Food and Drug Administration-approved drugs, including subconjunctival gentamicin and tobramycin. It is typically asymptomatic, with no apparent effect on visual function, and generally resolves after treatment discontinuation.…”
Section: In the Primary Efficacy Analysis Of This Study Ofmentioning
confidence: 99%
“…Among these, cornea verticillata (occasionally described as vortex keratopathy) is the most distinctive and prevalent clinical feature (Raizman et al. ). It is shown to be present in both hemizygous men and heterozygous women.…”
Section: Introductionmentioning
confidence: 99%